Anticancer and apoptosis-inducing effects of Moringa concanensis using hepG2 cell lines - V. Balamurugan; Veluchamy Balakrishnan; J. Philip Robinson; M. Ramakrishnan (Bangladesh Pharmacological Society, 2014)
The objective of the present investigation is focused on the anticancer activity of the ethanolic crude extract of Moringa concanensis leaf and bark against HepG2 cell line. The study was facilitated by collecting the plant sample and subjected to ethanol crude extraction. The anticancer activity of the crude extracted sample against HepG2 cell line was examined by MTT assay. The study confirms that the leaf crude extract of M. concanensis has pronounced anticancer potential against HepG2 cell lines while compared to that of the bark extract. The plant investigated possesses remarkable anticancer activity and hence isolation of the compound contributing to the activity may lead to develop at a novel and natural phytomedicine for the disease.